Civil Society and the Governance of Development - Uhlin, Anders. author. aut Link
XIII, 199 p.
Keywords: This book re-conceptualizes civil society engagement with global governance institutions in the field of development in terms of opposition. With an innovative theoretical framework, it maps and explains opposition strategies through detailed case studies on the EU, the Asian Development Bank, and the Global Forum on Migration and Development.